Dengue fever as a cause of hemophagocytic lymphohistiocytosis - Hein, Noely; Bergara, Gabriel Heiser; Moura, Nathalie Bianchini Vieira; Cardoso, Débora Morais; Hirose, Maki; Ferronato, Angela Espósito; Pastorino, Antônio Carlos; Lo, Denise Swei; Gilio, Alfredo Elias (Autopsy and Case Reports, 2015)
Dengue is endemic in more than 100 countries in Southeast Asia, the Americas, the western Pacific, Africa and the eastern Mediterranean regions. The virus is transmitted by Aedes mosquitoes. Dengue disease is the most prevalent arthropodborne viral disease in humans and is a global and national public health concern in several countries. A seasonal pattern of dengue disease is consistently observed. The highest incidences usually correspond to the period of highest rainfall and humidity, providing suitable conditions for Aedes aegypti breeding and survival. In Brazil for instance it is from January to June. Dengue may cause marked changes in bone marrow that result in hypocellularity and, consequently, thrombocytopenia and leucopenia, along with an increase in hematocrit, which is secondary to capillary leakage. However, those abnormalities are usually self-limited, and do not warrant further investigations, such as a marrow biopsy or a myelogram. The occurrence of persistent reactive hemophagocytosis is uncommon and usually leads to serious adverse outcomes. The authors report the case of an 8-year old girl complaining of high-grade fever, malaise, headache, abdominal pain and a cutaneous rash. Laboratory examination revealed atypical lymphocytosis on peripheral blood count, hyperbilirrunemia, abnormal liver enzymes and clotting tests. Serology was positive for dengue. Because of the persistence of fever and laboratory examinations were consistent with hemophagocytic lymphohistiocytosis (HLH) a bone marrow aspiration was performed, which confirmed the presence of hemophagocytosis. Hence we report a rare presentation of dengue accompanied by self-limited HLH that hopefully evolve to favorable outcome.